A Mística e suas Manifestações: uma reflexão fenomenológica sobre a mística especulativa a partir dos textos de São João da Cruz e Rûmi - Júnior, Reinaldo da Silva (Sacrilegens, 2006)
This article was born out of a playful exercise in the attempt to provide an answer to a research colleague who stirred me up to speak about speculative mysticism from a phenomenological perspective. Since I understand that the problem at the bottom of this question refers to the issue of epistemological barriers, I decided to deal with the subject so as to construct ways that make possible the dialogue between schools of thought which propose to study the mystical phenomenon. Starting from the principle that based on the instruments of human knowledge it is only possible to study the mystical experience in what it says from within its own language - since the experience in itself is ineffable -, I looked, starting from the texts of St. John of the Cross and Rûmi, and having in mind Lima Vaz’s construction of the concept of speculative mysticism, for points of contact between these universes of meanings.